2017
DOI: 10.1016/j.ultsonch.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic treatment of CoFe2O4@B2O3-SiO2 as a new hybrid magnetic composite nanostructure and catalytic application in the synthesis of dihydroquinazolinones

Abstract: New hybrid magnetic composite nanostructure are prepared via ultrasonic treatment by glass-ceramic method, characterized by field-emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), vibrating sample magnetometer (VSM), energy-dispersive X-ray (EDX), element distribution image (EDX mapping), thermal gravimetric analysis (TGA)/differential thermal analysis (DTA) and N adsorption-desorption by Brunauer-Emmett-Teller (BET) analyses. Then, the catalytic activity of the prepared CoFeO@BO-SiO nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Despite the good characteristics of the photocatalyst in water treatment, the lack of appropriate recovery of TiO 2 nanocomposites from treated water is a major problem when it comes to applying extensively. To overcome the problem of recovering catalytic nanoparticles from water, magnetic catalysts have been focused (Maleki and Kamalzare, 2014;Maleki et al, 2015;Maleki et al, 2016a;Maleki et al, 2016b;Maleki et al, 2017;Maleki et al, 2019b;Maleki et al, 2019c;Maleki et al, 2019a;Maleki et al, 2019d). After the water treatment process, the magnetic separation of Fe 3 O 4 /TiO 2 by using an external electromagnetic field recycles magnetic composites.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the good characteristics of the photocatalyst in water treatment, the lack of appropriate recovery of TiO 2 nanocomposites from treated water is a major problem when it comes to applying extensively. To overcome the problem of recovering catalytic nanoparticles from water, magnetic catalysts have been focused (Maleki and Kamalzare, 2014;Maleki et al, 2015;Maleki et al, 2016a;Maleki et al, 2016b;Maleki et al, 2017;Maleki et al, 2019b;Maleki et al, 2019c;Maleki et al, 2019a;Maleki et al, 2019d). After the water treatment process, the magnetic separation of Fe 3 O 4 /TiO 2 by using an external electromagnetic field recycles magnetic composites.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the particle size and morphology of nanostructure complex depended on temperature, power ultrasound and reaction time. Magnetic composites nanostructure is particularly attractive owing to their potential applications in catalysis due to their high catalytic performance as well as their easy separation and recycling 22–31 . Among various techniques for the synthesis of transition metal oxide nanoparticles such as impregnation, 32 co‐precipitation, 33 microwave heating, 34 and etc., thermal decomposition of inorganic complexes is one of the most common methods.…”
Section: Introductionmentioning
confidence: 99%
“…The increased attention on the use of novel catalyst and newer techniques via one pot multi component reactions led to the integration of a variety of novelty in their line of investigation [4][5][6][7]. The developments of newer catalyst which are in accordance with the principle of green chemistry are mostly used in one pot synthesis of heterocyclic compounds [8][9]. The direct use of commercially available biomolecules as a catalyst makes the processes simple and efficient and gains the significance over the conventional catalytic system, since their biocompatibility and known inclusive data about non-toxic nature allow them to enter into the category of catalyst and accepted as an environmentally suitable methodology.…”
Section: Introductionmentioning
confidence: 99%